GEOCHEMISTRY AND ORIGIN OF CORDIERITE ORTHOAMPHIBOLE ORTHO-PYROXENE PHLOGOPITE ROCKS FROM NAMAQUALAND, SOUTH-AFRICA - Moore, J; Waters, D (1990)
A suite of cordierite-orthoamphibole, cordierite-orthopyroxene and cordierite-phlogopite gneisses are described from the amphibolite-and granulite-facies region of the western Namaqualand Metamorphic Complex. The gneisses are directly associated with underlying ? and overlying metapelitic rocks to which they show certain geochemical affinities. Using overall geochemical trends and comparisons between amphibolite- and granulite-facies samples, particularly for Na2O, FeO and TiO2, a residual origin by extraction of granite melt can be excluded, and a premetamorphic origin proposed for the MgAlrich bulk compositions. The formation of these specific cordierite-orthoamphibole/orthopyroxene rocks by metamorphism of carbonate-associated evaporite sequences is not supported by their field relationships or by their AlFerich character. The bulk of the cordierite-orthoamphibole/orthopyroxene rocks have trace-element contents that strongly resemble those of underlying mafic rocks. An Al-rich group of cordierite-phlogopite-bearing rocks shows marked enrichment in Zr, Ce and Th, suggesting residual concentration following weathering. Major-element modelling of postulated premetamorphic constituents indicates that the majority of cordierite-orthoamphibole/orthopyroxene rocks comprise former mixtures of chlorite with lesser quartz and other minor clay components. Phlogopite-rich rocks can be modelled as mixtures of chlorite, illite and kaolinite. The suite probably formed by weathering of mafic volcanic material and its local redeposition in an environment where relatively warm, saline conditions favoured the development of chlorite-rich assemblages. © 1990.